AN OVERVIEW OF DHOKRA ART (BASTAR) PROGRESSION FROM ART TO DESIGN - Banerjee, Ujwal; Rani, Poonam (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Tribal Art and Craft, the pluralism of our nation that results from its diverse cultures. Every region possesses a unique artistic aesthetic. Most regions feature tribal arts and crafts in rural and indigenous areas. Chattisgarh is distinguished among the states due to its distinct folk and tribal cultures. Folk and tribal art and craft are manifestations of the pastoral way of life, religious convictions, and unpretentiousness of the people. Baster as a region of Chhattisgarh is characterized by its diverse communities, cultures, and artistic expressions. An area inhabited by numerous tribes that is remote from the progression of human civilization. Tribal lifestyle, caste system, and social rituals are all distinguishing characteristics that set these communities apart from others. Dhokraas an indigenous art form originated as part of the tribal life, and culture and uniquely reflects their community, rituals, and beliefs. The purpose of this paper is to present an overview on original form of craft, changes over time, and how the craft is being used in the design. The craft originated as part of the life of the tribal culture and reflects their community, rituals, and beliefs, and maintains a unique character. Over time the craft had gone through changes because of various influencing factors e.g., new requirements within their community, source of livelihood, artists and designers became interested in the craft, reach to the market, and support received from the Govt. The changes in the craft can be seen from various perspectives, from form, size, material, subject matter, and technique. The intention is to highlight progressive visual imagery, product design, and impact on the art form.